Pedestrianization around the San José market determining the walkability index - Tarquino Torres, Fernando Mauricio; Leon Ortiz, Alfredo; Sandoval Alfaro, Cesar (LACCEI, 2024)
The present study responds to the problem that afflicts the citizens of the Jesús María district, mainly those who live in the properties located around the San José market, due to the excessive use of street parking. In this sense, it is intended to improve the quality of life of residents, visitors and merchants in the area, promoting the pedestrianization of the streets located around the aforementioned supply center, by determining walkability indices and surveys that will support the proposals made. The project contemplates the elimination of parking on the streets adjacent to the market, and the creation of exclusive areas for pedestrian traffic, a measure that will allow pedestrians to walk with greater safety and comfort, in addition to promoting economic activity around the market, by create a more accessible, inclusive, healthy, resilient and sustainable environment.